Ways of Planning and Organizing Non-Traditional Forms of Texnology Lessons - Surobjonovna, Egamova Ravshanoy (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses technology lessons. It also provides information on educational technology aimed at developing students` creative abilities in a non-traditional way.